Antimicrobial activity of secondary metabolites produced by Aspergillus neobridgeri isolated from Pistacia lentiscus against multi-drug resistant bacteria (Bangladesh Journal of Pharmacology, 2020)
The in vitro antibacterial activity of the endophytic fungus Aspergillus neobridgeri PLR9 (isolated from the plant Pistacia lentiscus) against a wide range of tested bacteria were studied. The maximum inhibitory activity was found on malt extract agar medium with a mean inhibitory zone of 11.3 mm (p